Parametric beam modeling for reflector antennas - Venter, Mariet (Stellenbosch : Stellenbosch University, 2025)
Venter, M. 2025. Parametric Beam Modeling for Reflector Antennas. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/d797a472-0978-42d0-97ab-540d51d5f89f